Harmonization of Law in ASEAN Countries towards Economic Integration - Rajagukguk, Erman (Indonesian Journal of International Law, 2012)
Southeast Asia is a region rooted in cultural, ethnic, geographic and developmental diversity but generally viewed as a united block. The integration among ASEAN Countries becomes an avoidable demand in facing economic globalization. ASEAN Economic integration will be formed in ASEAN economic society in 2015. The economic integration among ASEAN countries emerged two problems: first, do the ASEAN countries need harmonization of law which correlates with the economic activities? Secondly, is the harmonization of law possible? This paper explores the need and possibility to increase the integration in the form of law and regulation to harmonize regional law, to allow ASEAN countries to function cooperatively and consistently among them and with the world.